The heart attack of the Polish health service: metaphors, arguments, and emotional appeals in political debates - Konrad Juszczyk; Barbara Konat; Małgorzata Fabiszak (Language and Cognition)
Metaphors, arguments and emotional appeals have considerable persuasive power in political discourse, yet they are rarely studied together. To explore the interactions between these interrelated phenomena, we employ three methods of analysis: Metaphor Identification Procedure, Inference Anchoring Theory, and lexicon-based sentiment analysis. Our data come from Polish political debates broadcasted during the 2019 pre-election campaign. We test hypotheses about the frequency of the associations between metaphors, arguments and emotional appeals. Hypothesis 1 predicts that arguments containing metaphors are more frequent than arguments without metaphors, hypothesis 2 predicts that arguments containing emotional appeals are more frequent than arguments without them, and hypothesis 3 predicts that arguments with metaphors and emotional appeals are more frequent than any other combination. The results show that metaphorical arguments do not outnumber non-metaphorical ones (H1 is falsified), and arguments that are both metaphorical and emotional do not outnumber the sum of all other types (H3 is falsified). Emotional arguments are more common than non-emotional ones (H2 is verified). We suggest that when political actors articulate their arguments, they often choose a particular metaphor to evoke positive or negative emotions in their audience.